Legal Review of the Easy of Giving Credit Facilities to Consumer Financing Institutions on the Prudential Principle - Kasiani Kasiani; Kasiati Kasiati (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
The research aims, (1), to determine the regulation of the prudential principle of consumer finance institutions in running their business with the principle of prudence. (2) to find out whether the provision of ease of requirements in obtaining consumer financing credit has taken into account the precautionary principle. The problem approach used in this research is by using a normative juridical research approach by studying library materials including legislation, articles and doctrinal opinions. Based on the results of the study, it shows that: (1) there is no legal umbrella regulating the precautionary principle in consumer finance institutions in running their business. (2) the provision of convenience in obtaining credit facilities to consumers is a form of non-implementation of the precautionary principle of consumer finance institutions in running their business, which in fact there is no law that regulates it, and results in harm to consumers. Keywords: Prudential Principles, Consumer Financing, Credit Facilities